The Influence of the Work Environment and Intrinsic Work Motivation on Employee Performance at the Minahasa Regency Central Statistics Agency - Pinontoan, Richi Cherio; Mandagi, Marthinus; Sendouw, Recky H.E (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This study aims to see how the influence of the work environment affects employee performance at the Minahas Regency Statistics Agency and Does intrinsic work motivation affect employee performance at the Minahasa Regency Statistics Agency? This type of research is expost facto with an associative quantitative approach with the aim of finding a causal relationship between variables based on the facts found by researchers. The results showed that there was a significant relationship between the Work Environment and Work Motivation on Employee Performance at BPS Minahasa Regency and there was a significant influence between the Work Environment and Work Motivation on Employee Performance at BPS Minahasa Regency. Variations in Employee Performance are influenced by variations in Work Environment and Work Motivation together.